Papers - Philadelphia Meeting – October, 1929 - Stability of Aluminum and Magnesium Casting Alloys (With Discussion) - A. J. Lyon (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1929)
The stability and permanence of any structural material used in aircraft are of paramount importance. The spontaneous hardening, or age-hardening, which takes place in some of the aluminum alloys under ordinary conditions of temperature and atmosphere, is accompanied by an increase in tensile strength and proportional limit and a decrease in elongation or ductility. Within the last few years the introduction of a number of strong and ductile casting alloys led to a study by the Materiel Division, Air Corps, of the permanence of the physical properties in several of these alloys. It has been found that even though some alloys have good properties directly after casting or heat treatment, they are not satisfactory for stressed parts that require a combination of strength and ductility. It has also led to the conclusion that all alloys that can be hardened by artificial aging—heating in a temperature range below 170" C. (340" F.)—will harden spontaneously if allowed to stand for a sufficient length of time. It follows that, in aircraft work where the factors of safety are limited on account of the necessity of keeping the weight of the structures as low as possible consistent with their safe operation, the properties of the alloys in the stable or final condition should be used as a basis for design rather than the properties obtained on the material directly after casting. The work of Wilm in Germany, Hanson and Gayler at the National Physical Laboratory in England, and Merica, Jeffries, and others in the United States, has shown that the spontaneous hardening is characteristic to a greater or less extent in all aluminum-base alloys in which the solubility in the solid state of the alloying constituents decreases with the temperature. It has been shown that, by heating to a temperature as near as possible to the melting point of the material and soaking at that temperature for a sufficient length of time and then quenching or cooling rapidly, a maximum amount of the soluble constituents can be retained in solution and the condition of maximum hardening effect upon aging can be obtained. Also, in ordinary sand and chill castings, without heat treatment, a sufficient amount of the alloying constituents is held in solution to cause important changes in the final physical properties.